The Educational Innovation Comparison of a Techno teaching Analysis in Primary School between Indonesia and Taiwan - Mochamad Yusuf Efendi; Suryawahyuni Latief; Hsieh Nancy Lien (Indonesia Approach Education, 2020)
The quality of education in Indonesia is still far from being expected. It is different from Taiwan. The government and people realize that a strong commitment to build and develop a national education system is a key determinant of the success of the state to maintain students’ achievement. The purpose of this study is to respond the correlation of teacher teaching experience (TTE) and instructional delivery on teacher’s competence (TCC), classroom curriculum (CC), and personal competencies (PC) by examining teachers in the primary schools from Taiwan and Indonesia. This study explores the differences between Taiwan and Indonesia cohort in TCC, CC, PC and correlation between TTE and TCC, CC, PC to bring learners` achievement. The results shown that the TCC, CC, PC are different from Taiwan and Indonesia. Then, TEE is statistically significant on TCC, CC, and PC. The techno teaching of each country is compiled by the ministry of education, and then the primary school is given the authority to develop techno teaching or students’ achievement in accordance with the conditions of each region and students’ demand in Indonesia which includes a teacher’s competencies that are supported to succeed the education especially in primary school.